Soviet partisan, 1941-44 - Cornish, Nik (Warrior, 2014)
The partisan war in the Soviet Union from 1941 to 1944 has been the subject of considerable political manipulation in the decades following 1945. In great part this was due to the need to project the image of a country united behind Joseph Stalin and the Communist regime when the truth was more complex than that. This book deals with this topic.